Scripting Hitchcock : Psycho, The birds, and Marnie - Raubicheck, Walter, 1950-; Srebnick, Walter (Urbana : University of Illinois Press, 2011)
Drawing from extensive interviews with the screenwriters and other film technicians who worked for Hitchcock, the authors illustrate how much of the filmmaking process took place not on the set or in front of the camera, but in the adaptation of the sources, the mutual creation of plot and characters by the director and the writers.
Preface -- The triptych and the screenplays -- The sources -- From treatment to script -- Final drafts : the shooting script -- Afterword.
Includes bibliographical references and index.
Description based on print version record.
English.
eBooks on EBSCOhost
Keywords: Hitchcock, Alfred, -- 1899-1980 -- Criticism and interpretation; Psycho (Motion picture : 1960); Birds (Motion picture); Marnie (Motion picture); Hitchcock, Alfred, -- 1899-1980; Birds (Motion picture); Marnie (Motion picture); Psycho (Motion picture : 1960); Motion picture plays, American -- History and criticism; Motion picture authorship; Film adaptations -- History and criticism; Screenwriters -- United States; Scénarios de cinéma américains -- Histoire et critique; Cinéma -- Art d'écrire.; Adaptations cinématographiques -- Histoire et critique; Scénaristes -- États-Unis.; Film adaptations; Motion picture authorship; Motion picture plays, American; Screenwriters; United States; PERFORMING ARTS -- Film & Video -- Direction & Production; PERFORMING ARTS -- Film & Video -- History & Criticism; Criticism, interpretation, etc; Electronic books